Parentage Verification and Segregation Distortion Patterns of Microsatellite Markers in Olive Flounder (Paralichthys olivaceus) Full-Sib Families - Songhyun Gwon; Eunjeong Kim; Wonse Lee; Jisung Han; Yoonkwon Nam (Animals)
Microsatellite markers are widely used in aquaculture for genetic analysis and breeding programs, but challenges such as segregation distortion and allelic instability can impact their effectiveness in parentage verification and inheritance studies. This study evaluated 15 microsatellite loci in seven experimental olive flounder (Paralichthys olivaceus) families bred through 1:1 full-sibling crosses, assessing their utility for accurate parentage and inheritance stability. Parentage assignments were conducted within an expanded pool of 647 candidate parents (including the actual 14 parents), encompassing both closely related and moderately distant individuals. Despite increased genetic diversity, assignments maintained a high accuracy rate (99.6%), demonstrating marker robustness. Differences in delta values highlighted the influence of genetic backgrounds on assignment clarity, with some groups showing reduced distinctiveness in the expanded pool. Segregation distortion was observed at certain loci, deviating from Mendelian inheritance, likely due to meiotic drive and post-zygotic selection. These findings underscore the need for empirical validation of microsatellite loci for stable inheritance and reliable parentage in diverse breeding programs, especially with genetically similar spawners.